Studies in Mexican Grasshoppers: Three new species of Dactylotini (Acrididae: Melanoplinae) from Mexico and a review of existing conspecifics with comments on their geographical distributions - Fontana, Paolo; Mariño-Pérez, Ricardo; Sanabria-Urbán, Salomón; Woller, Derek A. (Zootaxa, 2017)
Three new species of the tribe Dactylotini (Acrididae: Melanoplinae) are described from Central and Southern Mexico. 1) Dasyscirtus monicae sp. nov. Fontana, Mariño-Pérez, Sanabria-Urbán, & Woller is described from the eastern portion of the Balsas River Basin and the outer slope of the Mexican Volcanic Belt; 2) Perixerus obscurus sp. nov. Fontana, Mariño-Pérez, Sanabria-Urbán, & Woller is described from the Sierra Norte de Oaxaca mountain range; and 3), Perixerus triqui sp. nov. Fontana, Mariño-Pérez, Sanabria-Urbán, & Woller is described from the Sierra Madre del Sur mountain range and towards the Pacific Coast of Oaxaca. Taxonomic placement of these species is justified based on distinct morphology and comparisons with congeneric species are provided. Finally, we provide a biogeographical explanation for the distribution of the species in both genera.